Documentary heritage, memories and working history. The reconstruction of the Villa Carlos von Bernard case, Olavarría District, Buenos Aires, Argentina - Lemiez, Griselda; Endere, María Luz (Revista General de Información y Documentación, 2020)
In this paper the issue of documentary heritage in relation to the reconstruction of the history of companies is approached, taking as a case study the Villa Carlos von Bernard, in the Olavarría district, province of Buenos Aires, Argentina. In order to do this, we analyze the legal framework applicable to this heritage and the difficulties that arise when protecting private documentation. We also inquire about the social and cultural value of documents, in their different supports, as elements of cultural heritage and their link with historical reconstruction, mainly with the history of companies. The case demonstrates how, in the absence of documents of this factory, the historical reconstruction was made based on alternative sources, that is, journalistic, judicial, photographic, etc., supported and/or contracted with the oral memory of some of their protagonists. Finally, we wish to remember the role that documentary heritage plays in social memory and in democracies, for which we consider that it must be preserved and socialized. For this reason, it is a priority to have an adequate and updated regulatory framework to protect it.